2011
DOI: 10.1371/journal.pone.0027022
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Optic Disc Edema during Exposure to High Altitude Shows No Correlation to Acute Mountain Sickness

Abstract: BackgroundThe study aimed to quantify changes of the optic nerve head (ONH) during exposure to high altitude and to assess a correlation with acute mountain sickness (AMS). This work is related to the Tuebingen High Altitude Ophthalmology (THAO) study.Methodology/Principal FindingsA confocal scanning laser ophthalmoscope (cSLO, Heidelberg Retina Tomograph, HRT3®) was used to quantify changes at the ONH in 18 healthy participants before, during and after rapid ascent to high altitude (4559 m). Slitlamp biomicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…Studies in mountaineers revealed that an ascent to high altitude may cause morphological and functional changes of the retina, such as optic disc swelling, changes of macular function including color discrimination, altered retinal and choroidal blood flow, and retinal hemorrhages (Frayser et al, 1970;Wiedman, 1975;Pavlidis et al, 2005;Morris et al, 2007;Bosch et al, 2008Bosch et al, , 2009Willmann et al, 2010Willmann et al, , 2011Ho et al, 2011;Fischer et al, 2012). While some of these changes present physiological adaptive mechanisms to high altitude exposure such as increased blood flow and increased tortuosity of blood vessels, others present potentially pathological changes to hypoxia, such as optic disc swelling or retinal hemorrhages.…”
Section: High Altitude-associated Changesmentioning
confidence: 99%
“…Studies in mountaineers revealed that an ascent to high altitude may cause morphological and functional changes of the retina, such as optic disc swelling, changes of macular function including color discrimination, altered retinal and choroidal blood flow, and retinal hemorrhages (Frayser et al, 1970;Wiedman, 1975;Pavlidis et al, 2005;Morris et al, 2007;Bosch et al, 2008Bosch et al, , 2009Willmann et al, 2010Willmann et al, , 2011Ho et al, 2011;Fischer et al, 2012). While some of these changes present physiological adaptive mechanisms to high altitude exposure such as increased blood flow and increased tortuosity of blood vessels, others present potentially pathological changes to hypoxia, such as optic disc swelling or retinal hemorrhages.…”
Section: High Altitude-associated Changesmentioning
confidence: 99%
“…Also, the higher the ascent and the longer the duration at high altitudes, the higher the occurrence of retinal hemorrhages. Further studies have implicated that HARH may be seen more often in young and physically well-trained mountaineersespecially in those who undergo strenuous exercise at high altitudes (Brinchmann-Hansen et al, 1989;Arora et al, 2011)-such as in the report by Willmann et al (2011) where mountaineers rapidly ascended to an altitude of 4559 m.…”
Section: Incidence Timing and Location Of Harhmentioning
confidence: 99%
“…Whether high altitude retinopathy shows a clear correlation with cerebral dysfunction at high altitude and thus may be utilized as a predicting sign, is still a matter of debate (Clarke and Duff, 1976;Wiedman and Tabin, 1999;Barthelmes et al, 2011;Willmann et al, 2011). Hence, we suggest to discuss HARH separately from optic disc swelling, which has been included in the current classification of high altitude retinopathy (Wiedman and Tabin, 1999).…”
Section: Which Signs and Symptoms Of Altitude Illness Correlate With mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of this condition among climbers varies from 59% to 79% depending on the altitude above sea level and the speed of ascent. 37,38 There is a correlation between optic disk swelling, low arterial oxygen saturation, and the signs and symptoms of acute mountain disease. Hypoxia-induced brain volume increase is considered the most common cause of disk swelling at high altitudes.…”
Section: Management Strategy Of High-altitude Ocular Dysmotilitymentioning
confidence: 99%